Investor’s Perception towards Service Quality of DEMAT Account in Nepal - Dhodary, Shanker; Joshi, Shreeya (Pravaha, 2020)
The main purpose of the study is to analyze the investors’ perception towards service quality of DEMAT account in Nepalese capital market. The study has used descriptive research design to measure the perception towards service quality. This study is based on primary data by administered questionnaire to the investors. Service quality and customer satisfaction are interrelated. Higher the service quality, higher will be the customer satisfaction. The research findings, shows that investor’s perception towards service quality of DEMAT account meet Nepalese investor’s expectations and they are satisfied with the different features of DEMAT. Further, this study also shows that the most important predictor of investor satisfaction in this study is assurance dimension.